Atypical Femoral Fractures: Transverse Morphology at Lateral Cortex Is a Critical Feature. (March 2014) - Ng, Alvin C; Png, Meng Ai; Mohan, P Chandra; Koh, Joyce SB; Howe, Tet Sen
ABSTRACT In 2010, the American Society for Bone and Mineral Research (ASBMR) task force defined major and minor features to assist in the case finding and reporting of atypical femoral fractures (AFFs). One major feature that was proposed was a "transverse or short oblique configuration." Our primary aim was to compare the conventional overall fracture morphology (OFM) with its associated angle (OFMA) and our proposed lateral cortical fracture angle (LCFA) in the assessment of fracture configuration in suspected AFFs and non‐AFFs. The radiographs of 79 patients with AFFs and 39 patients with non‐AFFs were each analyzed by two blinded reviewers to obtain the OFM, OFMA, and LCFA. Using the overall fracture morphology to assess the suspected AFFs resulted in discordance between reviewers in 18 cases (22.8%), of which 5 (6.3%) were discordant between short oblique (>30° to 60°) and long oblique (>60° to 90°) configurations, therefore affecting their classifications as AFFs. By assessing only the critical component within the lateral cortex, all the suspected AFFs fell well within the classification as transverse fractures with a mean LCFA of 4.8° (range 0.3 to 18.0, SD = 4.23). The inter‐reader variability was also lower for LCFA versus OFMA (4.1° versus 6.9°, p = 0.001) when used to assess AFFs. Fracture angles were significantly different in AFFs versus non‐AFFs regardless of whether the OFMA or LCFA methodology was employed, but the greater difference associated with LCFA suggests its greater discriminating power. When LCFA was used in conjunction with 0° to 30° as the criteria for transverse morphology, all the AFFs and non‐AFFs were correctly classified. By using a standardized and precise method in measuring the fracture angle, specifically using only the component of the lateral cortex and limiting to truly transverse fractures, ie, between 0° and 30°, the LCFA is a robust and accurate method to assess the fracture morphology in suspected AFFs. © 2014 American Society for Bone and Mineral Research.